Transportation of Energy Resources in the Middle East and Central Asia - Saviolakis I. Panagiotis (International Journal of Energy Economics and Policy, 2013)
The current paper intends to analyze both the current and the emerging trends of the transportation of energy resources in the regions of Middle East and Central Asia. The means of land and sea transportation are examined in the light of both the financial changes and the geopolitics. Oil and natural gas are separately assessed with reference to both the areas of production and consumption as well as the relevant methods of transportation. Furthermore, bilateral relations between energy consuming countries, energy producing countries and countries that act as hubs for the transportation of these resources are evaluated in order to determine their influence in the current and future transportation trends. Suez Canal, Straits of Hormuz and the Straits of Bosporus and Dardanelles feature special characteristics that extend from the commercial field to politics and environmental. Statistical data are supplied to further comprehend the emerging market trends in these areas.